Recent Demographic Trends in Hungary and their Manifestation in Small Towns. - Pirisi, Gabor and Trocsanyi, Andras (2007)
Hungary, which is a recent entrant to the group of developed countries, is gradually assuming the demographic tenor of the group. An ageing and declining population, besides decreasing number of live births are commonly used terms for the demographic profile of Hungary. This simplified picture can be modulated with the help of spatial data to discern variations within. The widespread network of small towns could be a representative sample for the spatial investigation since it is spread over the whole country. Within the Hungarian context, settlements having less than 30,000 inhabitants and possessing an urban character can be defined as small towns. Due to their size and functions, small towns are sensitive enough to illustrate the national demographic tendencies, but they are numerous enough to be split into different groups according to their remarkably diverse character. Traditional historic small towns widely differ from the ones located in the rapidly urbanising agglomerations, even though the socialist new towns having similar origin also reflect significant demographic variants.